Stress management in organisations: theory and practice / Associate Professor Dato' Dr Wan Halim Othman (Universiti Teknologi MARA, Terengganu, 1991)
Stress has generally been regarded as a condition that is detrimental to our well-being and consequently as something that should be avoided in order to optimize performance and productivity. This is a common fallacy. In actual fact, a certain degree of stress is a physiological normal requirement for us to carry out most of our personal as well as job-related functions with optimal efficiency. This article discusses various levels of stress that human beings experience in relation to both our personal and professional lives. It also explains the physiological, psychological and behavioral components of stress, so as to give the reader a correct understanding of the subject. The final part of the article discusses some strategies that may be employed to cope with stress more effectively.